Integrating SMEs into the manufacturing value chain: an investigation of the challenges and opportunities for craft beer manufacturers in Gauteng, KwaZulu Natal & Botswana - Nkwanyana, Masetshedi (My University, 2020)
The contribution of small and medium enterprises (SME’s) and craft beer craft SME’s towards the economic development is well documented. Statistics have shown that craft beer SME’s contribute significantly towards employment in developed and developing countries the world over. In contrast, craft brewery SME’s in South Africa contribute marginally towards the economic development. One factor that has been identified as a solution is the integration of Craft Beer SME’s into the value chain. The purpose of the research study was to investigate the challenges and opportunities that craft beer SME’s encounter when attempting to integrate into the beer manufacturing value chain and how they strategically position themselves in order to entrench their sustainability. This research employed semi-structured interviews as the primary data collection tool. Purposeful sampling was used to select the participants and the data was organized into themes using the thematic analysis technique and analysed through a framework analysis method. The results of the research indicate that the main challenges of craft beer SME’s include shortage of funding to recapitalise and expand on operations which results in shortage on draught taps, lack of appropriate and consistent marketing strategies to drive beer sales sustainably and lack of economy of scales to produce beer with extended shelf life. The study established that several opportunities arise when craft breweries form strategic alliances with large commercial corporates. The alliance extend to having contracts with pubs and bars and being the supplier of beer at corporates such as events. The report recommends that it is imperative that craft breweries analyse and fully apprehend with their market specific value chain in order to understand how the key activities and key players affect their ability of integrating into the beer manufacturing value chain. The study concludes by proposing a conceptual business model framework that encompasses the integration of craft breweries into the beer manufacturing value chain
A research project submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Masters of Science in Engineering, 2020